Konstruks ilmiah Tafsir Secangkir Tafsir dalam Juz Terakhir Karya Salman Harun - umaiyatus syarifah (UIN Siber Syekh Nurjati Cirebon, 2022)
Â Secangkir Tafsir dalam Juz TerakhirÂ is an interpretation that written by academics as well as professor of UIN Syarif Hidayatullah Jakarta in the field of language and Tafseer.The scientific background, the life view of the mufassir, and the purpose of interpretationare very influential on the epistemology of interpretation. This article seeks to reveal the scientific construction of the interpretation of Salman Harun's work. The method used is descriptive analytical. This interpretation is a contemporary interpretation that combines historical and ra'yi interpretations using thematic methods, as well as a very dominant style of adab ijtima'i, using a contextual approach. This interpretation has a different nuance than the Indonesian interpretations in general. The presentation of language analysis, discussion that swoops in on social problems, plus the breadth of the exegetes' insight gives rise to moral messages related to current social-social problems which are presented briefly and concisely while still using the Quran and hadith as references in interpretation.